Kāvya sandarśanaṃ : Ācārya Divākarla Vēṅkaṭāvadhānigāri upanyāsamulu - Vēṅkaṭāvadhāni, Divākarla, 1913-1986 (Yuvabhārati pracurana ;, 1981)
Transcript of lectures on the Āmuktamālyada and the Pāṇḍuraṅgamāhātmyamu, 15th century Telugu poetical works.